Library Anxiety Among Marginalized University Students in Northeast India - Gogoi, Tripti; Singson, Mangkhollen; Thiyagarajan, S. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2021)
Objective – Library anxiety experienced by students has been discussed extensively for many decades. While the phenomenon is widely recognized, little attention has been paid to seeing its specific effect on marginalized sections of the society. The study attempts to understand the library anxiety experienced by students at three different universities in Assam. Assam is the only state in Northeast India to have private, state, and central universities. These universities draw their student populations from several different hill states in Northeast India, all of which face significant socio-political-economic challenges. Methods – A stratified random sample technique was used for the study. A total of 150 questionnaires were distributed equally among the three universities in Assam and found 119 questionnaires were fit for analysis. The study adopted the modified and validated version of the Bostick Library Anxiety Scale developed by Anwar, Al-Kandari, and Al-Qallaff (AQAK) in 2004, with 32 item statements and 4 categories. The questionnaire is divided into two parts: Demographic Variables and the Library Anxiety Scale. The categories used for the study were: Category 1 (Staff Approachability) – 11 statements; Category 2 (Feelings of Inadequacy) – 6 statements); Category 3 (Library Confidence) – 8 statements; and Category 4 (Library Constraints) – 7 statements. Results – The study hypothesized that factors such as gender, the language of instruction, type of university, and caste or community do not influence library anxiety among Northeast India students. However, the study's findings suggest that type of university influences library anxiety among students and its three constructs. Tezpur university students experience a higher level of library anxiety. Although no overall significant difference in the level of library anxiety was observed among students across gender (p=0.278, p> 0.05), the language of instruction (p=0.023, p> 0.05), castes and communities (p=0.223, p> 0.05), there was a significant difference in one construct of library anxiety among students based on gender (feelings of inadequacy), the language of education instruction (staff approachability), caste and community (feelings of inadequacy). Conclusions – Results from the present study provided compelling evidence to suggest that many students, irrespective of their gender, the language of instruction, type of university, discipline, and caste or community experience library anxiety. The difference levels of library anxiety among independent variables indicate a critical lack of information literacy skills. Overall, library anxiety scores among the students were moderate; some categories such as staff approachability, the feeling of inadequacy, and library constraint are the attributes of the students' anxiety. However, the findings of the study also suggest that students are confident in using the library. They are optimistic, enthusiastic, and keen to use library resources.